Design and Application of Duct Leak Detection Instrument in the Aircraft Pneumatic Systems - Irmayani; Unggul Prasetio; H. Heru Abrianto (Engineering And Technology Journal, 2024)
The pneumatic manifold system pipes on airplanes contain air with a pressure of approximately 45 psi and a temperature of approximately 117oC. This pipe stretches from the tip of the right wing to the tip of the left and continues to the tail area of ​​the aircraft. The total length of pipe reaches up to 300 meters. The diameter of the pipe reaches a size of up to 7 inches. Pneumatic system duct leaks are very dangerous because they affect aircraft performance and high temperatures can damage components around the leak and can even cause a fire. So far, if a leak is detected, it takes a long time to find the area because the detection method is still manual and visual. For this reason, a heat detection instrument was designed to find leak points in the pneumatic system channels. It is hoped that this instrument can help the process of finding leak points more quickly. The detection results of the instrument after testing its function using a heat sensor show more accurate results because the heat sensor can detect in areas that cannot be seen visually. This detection instrument is also able to measure the overheat temperature level at two stages, namely at 60°C and 100°C.